The study on the service quality and relation to customer satisfaction on logistic services in Sabah - Nur Faizilah Rizala; Sidah Idris (Faculty of Business, Economics and Accountancy Universiti Malaysia Sabah, 2023)
The competition among logistic companies has significantly increased, which has led these companies to strive to understand more about their customers’ needs and to maintain the customers’ satisfaction with the services that they offer, as online shopping has expanded dramatically during the COVID-19 endemic. This purchasing behaviour factor has also been driven by customers that are gaining the access to make a purchase decision only by using their gadgets at anytime and anywhere. This study aims to identify the relationship between online purchases to be related in the discussion of delivery, especially in the aspects of performance and service quality among logistic users. This study will employ literature analysis from previous research and find the gaps specifically in this area of concern. In total, 45 journal articles were involved in this analyses which came from various journals. The findings from this systematic literature research will be used for further research on this topic by extend it to an empirical study by using the quantitative method to analysis the findings from the perspective of the scope of this study. The significance of this study is expected to contribute to extend the current study in this area and will contribute to the managerial aspect of the logistic industry.